“And here we are, in the first cinema…”: “Coliseum” building in the memories of the residents of Sverdlovsk and Ekaterinburg - Anastasiia I. Voroshilova (Управление культурой)
Ekaterinburg is a cultural city where architectural structures such as the Coliseum Cinema reflect the historical development of the region. The Coliseum, one of the oldest buildings in the city, has been a place of attraction for citizens for 180 years and is an important cultural center. Urban space is formed through practices, ideas and images, while the collective memory of different generations of Coliseum visitors provides an opportunity to study these aspects. In anticipation of a major renovation of the building, recording the meanings of its existence over the past decades is of particular importance. In addition, the relevance of the study is due to the need to develop a brand strategy for the Provincial Dances contemporary choreography theater in this historically significant location. The article is devoted to the analysis of the memories of Coliseum visitors in order to identify its cultural and historical significance in the context of changing urban space and socio-cultural practices. The initiator of the study was the Provincial Dances Theater. The methods used were qualitative and quantitative approaches to collecting information. Biographical semi-structured interviews allowed us to collect narrative data on personal experiences and perceptions of the Colosseum, while an online questionnaire provided quantitative data to identify general trends in the perception of this cultural heritage site. A total of 25 interviews and 101 questionnaires were collected and processed in the fall of 2024. The sample included people who visited the Colosseum at different periods of its existence. The Colosseum is perceived as an important part of the urban space, acting as a landmark and a popular meeting place. Its location in the city center gives the building the status of a cultural center and a place of attraction. The building retains its symbolic meaning as a place of cultural exchange and communication, as well as a meeting space, which reflects the identity of the city's residents. The phenomenon of the Colosseum lies in its adaptation to the modern cultural context; it has remained a significant part of the public life of the metropolis for 180 years. In recent decades, the building has become an important venue for contemporary culture and dance, which must be taken into account when developing the development strategy for the Provincial Dances Theatre. The Coliseum is not only an entertainment venue, but also an important element of public life, contributing to the formation of social ties and cultural rituals.